LEUCITE BASANITES AND POTASSIUM SHONKINITES OF THE UGLOVOE BASIN, SOUTHERN PRIMORYE - Sakhno V.G.; Maksimov S.O.; Popov V.K.; Sandimirova G.P. (My University, 2004)
The development of potassic alkaline magmatism in southern Primorye was expressed in eruption of olivine-picroilmenite-leucite basanite along the NE-oriented extensional structure that was regenerated in the Miocene. This event predated the regional opening of pull-apart structures and large-scale plateau-basalt volcanism. The sequence of volcanic events presented in this communication is confirmed by the K-Ar data.